Implementasi Front-End Aplikasi Absensi Teknoid Menggunakan Tailwind CSS Studi Kasus ITB Ahmad Dahlan - Muhammad Hendrik Tarigan; Elliya Sestri (Jurnal Teknologi Informasi (JUTECH), 2026)
The digital transformation in higher education institutions demands more efficient administrative systems, including staff attendance systems. ITB Ahmad Dahlan still faces challenges with its current attendance system, such as manual recapitulation, undeleted inactive employee data, and limited automation features. This study aims to implement the front-end interface of a web-based attendance system using Tailwind CSS with an Agile approach. The system is designed to be responsive, modular, and integrated with features such as attendance validation, employee account management, and automated recapitulation. The development process includes requirement analysis, interface design, implementation with an organized folder structure, and functionality testing through Black Box and System Usability Scale (SUS) methods. The test results indicate that the system is accessible across various devices, performs well, and receives positive feedback from users. This front-end implementation is expected to support administrative efficiency and serve as a foundation for future integration with RFID- and IoT-based attendance systems.